2010
DOI: 10.1177/1367006910379263
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological responses to the emotional and taboo Stroop tasks in native and non-native speakers of English

Abstract: Skin conductance levels (SCLs) of native and non-native English speakers were measured during emotional and taboo Stroop tasks. Significantly slower response times to negative and taboo words when compared to neutral words were found in both groups of participants, but positive words were not found to differ significantly from neutral words. No differences between native and non-native speakers in their behavioural responses were present: the pattern of interference from negative and taboo words was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
133
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 29 publications
18
133
2
Order By: Relevance
“…The other three studies that measured the emotional effects worked with late bilinguals, who started to learn the second language at the age of 6-7 or later (Eilola et al 2007;Eilola & Havelka 2010b) and in formal, educational settings (Winskel 2013). Eilola et al (2007) and Eilola and Havelka (2010b) have found mutually concurring results: a significant effect of word type, and non-significant effects of language and interaction.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The other three studies that measured the emotional effects worked with late bilinguals, who started to learn the second language at the age of 6-7 or later (Eilola et al 2007;Eilola & Havelka 2010b) and in formal, educational settings (Winskel 2013). Eilola et al (2007) and Eilola and Havelka (2010b) have found mutually concurring results: a significant effect of word type, and non-significant effects of language and interaction.…”
Section: Discussionmentioning
confidence: 91%
“…The authors' main conclusion was that the impact of the age of language acquisition was not as important as the proficiency level of a later acquired language for the emotional salience of a language. Eilola and Havelka (2010b) have continued their work in this field; in a new research they compared English native speakers with Greek-English late, Greek dominant bilinguals. The difference was that only English was tested: in one group as a native and in the other group as a second language.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ratings for the 3 taboo items in English ("He's an asshole", "He screwed your mother", "She's a bitch") received slightly higher ratings than the corresponding Mandarin items (p. 342), but skin conductance responses for insults, reprimands and taboo words were comparable in both languages. Skin conductance responses have been combined with reaction times in Eilola and Havelka (2011). The authors investigated a group of 32 native English speakers and a group of 31 bilinguals (Greek-English) who were students at the University of Kent (UK) using emotional and taboo Stroop tasks.…”
Section: Emotion and Swearing In Multilingual Contextsmentioning
confidence: 99%